Immune responses to a single dose of the AZD1222/Covishield vaccine in health care workers - Chandima Jeewandara (Nature Portfolio, 2021)
Here the authors show in a large cohort of healthcare workers that one dose of the AZD1222 vaccine seroconverts 92.9% of vaccinees, irrespective of age and gender, and results in high antibody titers to wild-type SARS-CoV-2 but only low titers to the B.1.351 variant.